Effects of a Literacy Feature in an Augmentative and Alternative Communication App on Single-Word Reading of Individuals with Severe Autism Spectrum Disorders. (March 2021) - Caron, Jessica; Light, Janice; McNaughton, David
The purpose of this study was to investigate the effects of an augmentative and alternative communication (AAC) app with transition to literacy (T2L) software features (i.e., dynamic text and speech output upon selection of a graphic symbol within the grid display) on the acquisition of 12 personally relevant single words for individuals with severe autism spectrum disorder (ASD) who had minimal or no speech. The study implemented a single-subject, multiple-probe, across word sets design with four participants. All four participants in this study demonstrated increased accuracy reading targeted single words and results from this study provide preliminary evidence that the T2L features can positively affect the single-word learning of individuals with ASD who have minimal speech and limited literacy skills.